Respiratory dysfunction in whiplash associated disorders (WAD) with cervical plexus syndrome – A case report - NA Nystrom; SR Daulat; A Zakaria; M Petersen; VM Moodley; LP. Champagne (Surgery in Practice and Science)
Whiplash Associated Disorders (WAD) represents a chronic post-traumatic pain syndrome from indirect flexion-extension trauma to the neck. The condition exhibits significant variability among affected individuals and can involve numerous secondary symptoms, including but not limited to myalgia, central sensitization, migraines, photophobia, jaw pain, dysphagia, joint stiffness, and tinnitus, while significant breathing problems are not commonly associated with or prominently considered in WAD.Herein, we present the diagnosis and successful surgical treatment of severe respiratory dysfunction and staccato speech in a patient with WAD, who over a period of more than ten years underwent multiple spirometry evaluations for breathing difficulties that correlated with the severity of neck pain. In 2019, his condition deteriorated, with significantly increased pain and dyspnea leading to further evaluations that included laboratory studies and consultations with specialists in neurosurgery, neurology, pulmonology, neurophysiology, ENT, general internal medicine, cardiology, radiology, speech pathology, physical medicine, orthopedic surgery, and hand surgery at three separate academic centers in Norway.Eventually, the patient was diagnosed with a condition that is regularly observed among patients referred to our office for evaluation and surgical treatment of chronic, whiplash related pain, and that we propose to label Cervical Plexus Syndrome.One year following exploration and neurolysis of sensory nerves to the right and left superficial cervical plexus, the patient remains pain free, with unimpeded speech and breathing as demonstrated by postoperative spirometry and video recordings.Although the underlying pathophysiology remains unclear, we report what we believe to be the first successful surgical treatment of serious respiratory dysfunction from pain generators in tissue that historically is considered anatomically and functionally separate from the mechanics of breathing. Further investigation will be needed to determine prevalence of respiratory dysfunction in chronic neck pain.